Recombinant Photolyase-Thymine Alleviated UVB-Induced Photodamage in Mice by Repairing CPD Photoproducts and Ameliorating Oxidative Stress - Zhaoyang Wang; Ziyi Li; Yaling Lei; Yuan Liu; Yuqing Feng; Derong Chen; Siying Ma; Ziyan Xiao; Meirong Hu; Jingxian Deng; Yuxin Wang; Qihao Zhang; et al. (MDPI AG, 2022)
Cyclobutane pyrimidine dimers (CPDs) are the main mutagenic DNA photoproducts caused by ultraviolet B (UVB) radiation and represent the major cause of photoaging and skin carcinogenesis. CPD photolyase can efficiently and rapidly repair CPD products. Therefore, they are candidates for the prevention of photodamage. However, these photolyases are not present in placental mammals. In this study, we produced a recombinant photolyase-thymine (rPHO) from Thermus thermophilus (T. thermophilus). The rPHO displayed CPD photorepair activity. It prevented UVB-induced DNA damage by repairing CPD photoproducts to pyrimidine monomers. Furthermore, it inhibited UVB-induced ROS production, lipid peroxidation, inflammatory responses, and apoptosis. UVB-induced wrinkle formation, epidermal hyperplasia, and collagen degradation in mice skin was significantly inhibited when the photolyase was applied topically to the skin. These results demonstrated that rPHO has promising protective effects against UVB-induced photodamage and may contribute to the development of anti-UVB skin photodamage drugs and cosmetic products.